The effect of 4 weeks of strength training and beta-alanine supplementation on anaerobic power and carnosine level in boxer players - Alabsi, K.; Rashidlamir, A.; Dokht, E. H. (Journal of Science in Sport and Exercise, 2023)
Purpose: The objective of this study was to investigate the effect of 4 weeks of strength training with beta-alanine supplementation on anaerobic power and carnosine level in boxer players. Methods: Eighteen male boxer players participated in this study, randomly divided into two homogeneous groups (strength training + beta-alanine and strength training + placebo groups). The study design was double-blind, parallel, and placebo-controlled. An anaerobic Wingate test was performed by athletes before and after the intervention period (4 weeks). Participants received 0.3 g/kg of body mass of the supplement (maltodextrin or beta-alanine) per day during the intervention. Participants were also evaluated for anaerobic power, serum level of carnosine, and blood lactate before and after 4 weeks. Results: Average power in both groups was significantly increased compared with pre-intervention, but fatigue index was significantly decreased only after beta-alanine supplementation; however, there were no significant differences with either average power or fatigue index between the beta-alanine and placebo groups. There was no significant difference in the interaction between the groups and time, as well as no significant difference between groups for lactic acid. Carnosine level in both groups was significantly increased compared with pre-intervention. When changes in serum carnosine for the two groups were examined, statistical analysis showed a significant difference between the beta-alanine and placebo groups. Conclusion: Four weeks of strength training accompanied by beta-alanine supplementation had a likely beneficial effect on boxer players' anaerobic performance and carnosine level.